EFEKTIVITAS PERMAINAN BUILDING BLOCK DALAM MENSTIMULASI KECERDASAN VISUAL SPASIAL ANAK KELOMPOK B TK AL-WASHLIYAH ALUE NAGA BANDA ACEH - Cut Fazlil Hanum; Lidia Yeni Marliana (Jurnal Buah Hati, 2017)
Game building block is a game where the child can make konstruksional skills and expand imajinasi Majesty in making/planning a building from various forms of the lego. The result of which was the beginning of the second, only 2 (374 ft) children can identify colors with true and doubtful again, this aspect of strain measurement, the names of shapes and menuangkan ideas in the form of plan, all children are still experiencing difficulties where all children are still yet to develop. This review uses experimental observations. Type of review of the experiments the authors use yaitu one-group pre-test-post-test design. Based on the review results can be stated that a game of Building Block Effective in stimulating the visual intelligence spasial the son of cluster B kindergarten Al-Washliyah Alue Naga Banda Aceh. The research results obtained based on T-test such significant extent at α = 0.05 and dk = 12 criteria receive H0 if = 1/2-α (n-1) ttable = t (1-0.025) (12) = t (0,975) (12) = 11.7. And reject H0 if t has a value to another. From the table of distribution obtained t (0,975) (12) = 11.7 because ttest meets the criteria –t−12 ᾳ (n-1) < ttable t1 −12 ᾳ (n-1) (ttest > ttable) = 17, 46 > 11,7 H0 is rejected and then accepted the H1. It means the game Building Block is effective in Stimulating the visual spatial intelligence group B kindergarten Al Washliyah Alue Naga Banda Aceh.